Internal nasal dilator in patients with obstructive sleep apnea - Gelardi, Matteo; Intiglietta, Pierluigi; Porro, Giuseppe; Quaranta, Vitaliano Nicola; Resta, Onofrio; Quaranta, Nicola; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2019)
The nasal valve area has the minimal cross-sectional area of the upper airways. Obstructive sleep apnea (OSA) is a common disorder. It has been reported that nasal obstruction may be associated with OSA. The aim of this study was to investigate whether the use an internal nasal dilator may be able to affect respiratory pattern in a group of patients with OSA. The use of internal nasal dilator was able to significantly reduce two relevant respiratory outcomes, such as the apnea-hypopnea index and the oxygen desaturation index, notably there was also a positive trend for the reduction of total sleep time with HbO2